Changes in Malay Traditional Law From A Sociological and Legal Anthropological Perspective - Yovani Zela; Ending Solehudin (Program Pascasarjana UIN Sumatera Utara Medan, 2020)
This study aims to analyze changes in Malay customary law from the perspectives of legal sociology and legal anthropology, and to identify the factors influencing these changes. Malay customary law, as living law, is a system of norms that grows and develops within society, regulating various aspects of life such as marriage, inheritance, and social relations. Over time, customary law has undergone transformation due to the influence of Islam, colonialism, modernization, and globalization. This study uses a deductive method with a normative approach based on a review of relevant literature and legal materials. The research results show that Malay customary law has undergone both normative and socio-cultural shifts. From a legal sociology perspective, these changes are influenced by the dynamics of social structures and the dominance of state law, often resulting in customary law being subordinate to positive law. Meanwhile, from a legal anthropology perspective, these changes occur due to transformations in values, lifestyles, and cultural interactions within the community. Nevertheless, Malay customary law remains a cultural identity that continues to adapt to the needs of modern society. Thus, changes in Malay customary law represent a form of adaptation to changing times, but also pose challenges in maintaining the continuity of traditional values. Therefore, synergistic efforts between the community, government, and customary institutions are needed to preserve the existence of customary law in national legal life.